Bronchiectasis in COPD patients: more than a comorbidity? - Martinez-Garcia, Miguel Angel (Int J Chron Obstruct Pulmon Dis, 2017)
Computed tomography scan images have been used to identify different radiological COPD phenotypes based on the presence and severity of emphysema, bronchial wall thickening, and bronchiectasis. Bronchiectasis is defined as an abnormal dilation of the bronchi, usually as a result of chronic airway inflammation and/or infection. The prevalence of bronchiectasis in patients with COPD is high, especially in advanced stages. The identification of bronchiectasis in COPD has been defined as a different clinical COPD phenotype with greater symptomatic severity, more frequent chronic bronchial infection and exacerbations, and poor prognosis. A causal association has not yet been proven, but it is biologically plausible that COPD, and particularly the infective and exacerbator COPD phenotypes, could be the cause of bronchiectasis without any other known etiology, beyond any mere association or comorbidity. The study of the relationship between COPD and bronchiectasis could have important clinical implications, since both diseases have different and complementary therapeutic approaches. Longitudinal studies are needed to investigate the development of bronchiectasis in COPD, and clinical trials with treatments aimed at reducing bacterial loads should be conducted to investigate their impact on the reduction of exacerbations and improvements in the long-term evolution of the disease.